Interspeech 2021 2021
DOI: 10.21437/interspeech.2021-1588
|View full text |Cite
|
Sign up to set email alerts
|

Anonymous Speaker Clusters: Making Distinctions Between Anonymised Speech Recordings with Clustering Interface

Abstract: Our study examined the performance of evaluators tasked to group natural and anonymised speech recordings into clusters based on their perceived similarities. Speech stimuli were selected from the VCTK corpus; two systems developed for the VoicePrivacy 2020 Challenge were used for anonymisation. The Baseline-1 (B1) system was developed by using x-vectors and neural waveform models, while the Baseline-2 (B2) system relied on digital-signal-processing techniques. 74 evaluators completed three trials composed of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…By instructing participants to sort 32 stimuli into 1 to 32 different speaker groups, Johnson et al suppressed the possibility of introducing artificial bias [21]. Recently O'Brien et al [44][45][46] developed a perceptual clustering method and reported unfamiliar listeners were effective at navigating the intuitive interface.…”
Section: Perceptual Speaker Identification Tasksmentioning
confidence: 99%
“…By instructing participants to sort 32 stimuli into 1 to 32 different speaker groups, Johnson et al suppressed the possibility of introducing artificial bias [21]. Recently O'Brien et al [44][45][46] developed a perceptual clustering method and reported unfamiliar listeners were effective at navigating the intuitive interface.…”
Section: Perceptual Speaker Identification Tasksmentioning
confidence: 99%